Crystallization-Driven Optimization of Morphology and Performance in Near-Infrared Organic Photodetectors via Alkyl Side Chain Tuning of Narrow Bandgap Non-Fullerene Acceptors - Cho, Kyounguk; Ha, Jong Woon; Nam, Minwoo; Lee, Chihyung; You, Seung Ju; Lee, Ah Young; Yoon, Sung Cheol; Han, Mijeong; Kim, Jong H.; Ko, Seo Jin; Ko, Doo Hyun (Advanced Functional Materials, 2024)
Narrow bandgap non-fullerene acceptors (NBG NFAs) are crucial in advancing near-infrared organic photodetectors (NIR OPDs). However, the polymorphous behavior of NFAs introduces energetic disorder and charge-trapping sites in the bulk heterojunction (BHJ) active layers, thereby hindering the NIR performance of OPDs. This study demonstrates the design and optimization of the molecular structures of alkyl side chains in NFAs to morphologically address these electrical limitations and shed light on how side chains affect the crystallization-driven control of the morphogenesis process in BHJ layers. The structure, linearity, and length of the alkyl side chain molecules are strategically designed and controlled to synthesize a series of NBG NFAs, namely COT-R (R = EH, BO, Oct, or Dod). The in-depth quantitative investigations into the morphological and electrical factors reveal that side-chain optimization effectively enhances various morphological properties, such as the molecular alignment and compatibility between components in the BHJ layer, resulting in the mitigation of energetic disorders and charge traps in the BHJ layers. Therefore, the optimized BHJ system, comprising COT-Oct blended with PTB7-Th, achieves a reduced dark current and increased responsivity, contributing to the development of high-performance NIR OPDs with an impressive specific detectivity of 1.49 × 1012 Jones at 1000 nm under -0.5 V.
Keywords: Bulk heterojunction; Energetic disorder; Infrared detection; Near Infrared; Near-infrared; Near-infrared detection; Non-fullerene acceptor; Organic photodetector; Organics; Performance; energetic disorder; morphology; near-infrared detection; non-fullerene acceptor; organic photodetector